Sentencing scammers: law and practice - Lorana Bartels
The Australian Bureau of Statistics (ABS) (2008: 5) has defined consumer scams as a fraudulent invitation, request, notification or offer, designed to obtain someone’s personal information or money or otherwise obtain a financial benefit by deceptive means